DETERMINAN PEMILIHAN METODE KONTRASEPSI JANGKA PANJANG PADA AKSEPTOR KB AKTIF DI PUSKESMAS PEDAMARAN - Lusia Weni; Muhammad Yuwono; Haerawati Idris (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2019)
Determinant of the selection of long-term contraceptive methods on family planning acceptors in Pedamaran community health center.  The population problem faced by Indonesia is a large population with a low quality of life. Uncontrolled population rate will cause baby booming so information needs to be disseminated about the benefits of family planning (FP). Long-term contraceptive method has a high level of effectiveness and can reduce the rate of population growth. This study aim to determine the factors that affect the selection of long-term contraceptive methods in active family planning acceptors.This study used a cross-sectional study design and using simple random sampling technique, consisted of 243 acceptors. Analyzes of data were univariate analysis, bivariate analysis using chi-square test with α = 0.05 and 95% confidence interval value, and multivariate analysis using binary logistic regression.Based on multivariate analysis was the variables significantly related to the selection of long-acting contraception include age (p = 0.01; OR = 2,24; 95% CI: 1,17-4,29), education (p = 0.01; OR = 0,31; 95% CI: 0,13-0,75) and number of children (p = 0.03; OR = 2; 95% CI: 1,05-3,81). Thus, age was the variable that had the greatest impact on determining the selection of long-acting contraception.The acceptors with ≥ 35 years old, low educated and have >2 children more likely to choose long-acting contraception. It is hoped that family planning workers can educate and persuade people of all ages with different educational backgrounds so total fertility rate can be reduce.